Informal Agency Rulemaking and the Courts: A Theory for Procedural Rreview - Cooley R. Howarth Jr. (Washington University Law Quarterly, 1984)
This Article will demonstrate that judicial review of agency rulemaking procedures, if properly structured, is an acceptable and important tool for the control of regulatory policy-making. The procedural discretion of administrative rulemakers should not be as broad as Vermont Yankee suggests. The first part of this Article will identify the procedural values which should serve as normative guides to the adequacy and legitimacy of informal rulemaking. The second part will examine the Supreme Court's opinion in Vermont Yankee, criticizing its approach to procedural review of informal rulemaking as a threat to the integrity of that rulemaking process. In the third section of the Article, the judicial and scholarly reactions to Vermont Yankee will be examined and critiqued. It is clear that neither the courts nor the commentators have yet succeeded in developing an approach to procedural review of informal rulemaking which adequately responds to the problems created by Vermont Yankee. The Article will conclude with a suggested theory for procedural review of informal rulemaking. This theory will present an instrumental interpretation of section 553 of the APA which establishes the minimum procedural requirements needed to preserve the procedural values that insure the integrity of informal rulemaking. The theory will also outline a method and supporting rationale for judicial review of the discretionary procedural decisions of agency rulemakers—decisions by agencies to employ (or not employ) additional rulemaking procedures beyond those minimally required by the APA.
Keywords: Vermont Yankee Nuclear Power Corp. v. Natural Resources Defense Council 435 U.S. 519 (1978); Administrative procedure; Judicial review of administrative acts; Administrative Procedure Act; United States